2021
DOI: 10.1136/bmjgh-2021-005019
|View full text |Cite
|
Sign up to set email alerts
|

The cost and intermediary cost-effectiveness of oral HIV self-test kit distribution across 11 distribution models in South Africa

Abstract: BackgroundCountries around the world seek innovative ways of closing their remaining gaps towards the target of 95% of people living with HIV (PLHIV) knowing their status by 2030. Offering kits allowing HIV self-testing (HIVST) in private might help close these gaps.MethodsWe analysed the cost, use and linkage to onward care of 11 HIVST kit distribution models alongside the Self-Testing AfRica Initiative’s distribution of 2.2 million HIVST kits in South Africa in 2018/2019. Outcomes were based on telephonic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Viewers were typically sceptical about the opportunity to access HIVST and PrEP in their area of Eastern Cape, despite recent investments in HIV self-test and PrEP distribution. 22 The survey showed that DS2 viewers were more likely than non-viewers to have paid a fee for their last HIV self-test kit, suggesting that the ability to pay or access a pharmacy may help to explain the observed differences in use of self-testing, even if MTV Shuga boosted motivation for HIV testing. To ensure equitable access to prevention tools and services, media campaigns that generate demand should be directly linked to distribution efforts that are available and acceptable to young people.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Viewers were typically sceptical about the opportunity to access HIVST and PrEP in their area of Eastern Cape, despite recent investments in HIV self-test and PrEP distribution. 22 The survey showed that DS2 viewers were more likely than non-viewers to have paid a fee for their last HIV self-test kit, suggesting that the ability to pay or access a pharmacy may help to explain the observed differences in use of self-testing, even if MTV Shuga boosted motivation for HIV testing. To ensure equitable access to prevention tools and services, media campaigns that generate demand should be directly linked to distribution efforts that are available and acceptable to young people.…”
Section: Discussionmentioning
confidence: 99%
“…An important limitation to a multimedia campaign like MTV Shuga is its lack of influence on supply of services, either actual or perceived supply, including the HIV prevention technologies it promoted through DS2. Viewers were typically sceptical about the opportunity to access HIVST and PrEP in their area of Eastern Cape, despite recent investments in HIV self-test and PrEP distribution 22. The survey showed that DS2 viewers were more likely than non-viewers to have paid a fee for their last HIV self-test kit, suggesting that the ability to pay or access a pharmacy may help to explain the observed differences in use of self-testing, even if MTV Shuga boosted motivation for HIV testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of workplaces were included: (a) larger companies that did not have formalized HIV testing programs or had a significantly low HIV testing uptake. These companies were contacted before the distribution event for sensitization; (b) smaller workplaces, such as petrol stations or construction sites, without prior arrangement with management [14].…”
Section: Workplace Hivst Distribution and Data Collectionmentioning
confidence: 99%
“…Most of the empirical evidence on the cost of self-testing programmes originates from the human immunodeficiency virus (HIV) self-testing literature,6 9 10 and more recently from hepatitis C virus (HCV) self-testing 11. Studies have demonstrated the relative cost of different methods for rollout of HIV self-testing and found, broadly, that there are multiple ways of successfully distributing HIV self-testing, depending on the budget and desired outcome.…”
Section: Introductionmentioning
confidence: 99%